2008
DOI: 10.3174/ajnr.a1102
|View full text |Cite
|
Sign up to set email alerts
|

Late Evaluation of Silent Cerebral Ischemia Detected by Diffusion-Weighted MR Imaging after Filter-Protected Carotid Artery Stenting

Abstract: BACKGROUND AND PURPOSE:Postoperative diffusion-weighted MR imaging (DWI) often discloses new lesions after carotid artery stent placement (CAS), most of them asymptomatic. Our aim was to investigate the fate of these silent ischemic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 22 publications
7
32
0
9
Order By: Relevance
“…This result compares favorably with previous reports that reveal a number of silent ischemic lesions after neuroprotected CAS, ranging from 15.3% to 50%. 32,33 This finding supports the idea that less device manipulation, including CPDs, across the lesion minimized emboli dislodgment.…”
Section: Discussionsupporting
confidence: 76%
“…This result compares favorably with previous reports that reveal a number of silent ischemic lesions after neuroprotected CAS, ranging from 15.3% to 50%. 32,33 This finding supports the idea that less device manipulation, including CPDs, across the lesion minimized emboli dislodgment.…”
Section: Discussionsupporting
confidence: 76%
“…2 In line with previous studies, acute lesion volume was the only predictor for lesion persistence. 7,[9][10][11] This finding is in line with the clinical observation that in ICSS, most periprocedural clinical strokes associated with stenting recovered quickly and there was no difference in the proportion of patients with disabling symptoms after 1 month. 12 The most important limitation of our study was the lack of power to perform interaction tests investigating whether risk factors for lesions differed significantly between treatment groups.…”
Section: Discussionsupporting
confidence: 76%
“…White matter disease might be considered an indicator for increased vulnerability of the brain toward periprocedural embolism. 6 In previous reports, the proportion of brain lesions persisting on follow-up FLAIR imaging ranged from 3% to 40% after stenting [7][8][9][10] and was 33% after endarterectomy. 10 In contrast to these studies, we were able to compare the rate of conversion from acute to persisting lesions between patients randomized to stenting or endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, smaller DWI lesions are more likely to be reversible and more often remain clinically silent compared with larger lesions. 20,21 The impact of silent DWI lesions on cognition is the subject of current research. In line with 2 other studies, 22,23 a single-center substudy in ICSS revealed a small but statistically significant decrease in global cognitive performance 6 months after CAS compared with baseline values, an effect that was not present in the CEA arm.…”
Section: Strokementioning
confidence: 99%